Climate Services supporting the adoption of Climate Smart Agriculture: Potential linkages between CSA adoption and climate services use - Born, Lorna (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
Climate services (CS) are defined by Vaughan et al. (2018) as “the production, translation, transfer and use of climate knowledge and information in climate-informed decision-making and climate-smart policy and planning”. CS support adaptation to climate variability and change in agriculture by informing farmer and institutional decision- making, producing local climate knowledge, supporting efforts to build resilience and manage climate risk, and improving the enabling environment for Climate Smart Agriculture (CSA) adoption (Hansen et al., 2019). CSA practices target the three CSA pillars; increasing adaptation/resilience to climate change, increasing food production and, where feasible, mitigating greenhouse gas emissions (Aggarwal et al., 2018). CSA falls under Flagship 1 in CCAFS and climate services under Flagship 4.